0765 Parental Goals for Infant and Toddler Sleep. (27th April 2018) - Mindell, J A; Leichman, E
Abstract: Introduction: The aim of this study was to assess parent perceptions of their child's sleep and sleep-related goals, regardless of sleep quality. Methods: Caregivers (97.6% mothers) of 807 infants and toddlers (birth to 37 mos; M = 16.5 months; 49.0% male) reported on child sleep patterns and problems via an online survey. The survey included an abbreviated version of the Brief Infant Sleep Questionnaire, and a list of potential sleep-related areas of change. Results: 29.1% of caregivers reported a perceived sleep-problem, whereas 90.1% indicated an area of desired change related to their child's sleep. Overall, parents most commonly wanted their child to sleep for longer stretches overnight (19.4%). An additional 14.1% of parents wanted an earlier bedtime or later morning wake time. Further, 10.4% wanted their child to fall asleep independently or without a specific sleep aid (12.1%; e.g., pacifier, feeding, swaddle, music). As expected, more parents indicated that they wanted to change something about their child's sleep if they endorsed a sleep problem (99.5%), as compared to those who did not endorse a sleep problem (87.1%), p<.05. Parents who noted a sleep problem primarily wanted to reduce night wakings (34.5%) and help their children learn to fall asleep independently (17.3%) or without nursing (9.3%). Parents who did not indicate a problem focused on sleep scheduling, such as earlier bedtimes (8.1%) and later wake times (9.6%). Conclusion: Although one-third of parents of young children indicate a perceived sleep problem, almost all parents wish to change something about their child's sleep. The most common areas of change relate to falling asleep independently, night wakings, and sleep schedules. Sleep education and assessment delivered by health care providers should focus not only on what families consider to be "problematic, " but also what families would like to modify, or improve, about their child's sleep. Support (If Any): Funding: Johnson & Johnson Consumer Inc., Skillman, NJ, USA.